By-and-by : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Hollow, Caroline-Anne (Massey University, 2021)
This exegesis elaborates upon the growth and exploration of my artistic practice within this thesis project. I have endeavoured to explore the idea of ‘by-and-by’ (before long; eventually) in action within my making. Through the action of embodied walking, a constant cycle of choices and actions have resulted in iterations forming bursts of learned growth – including pauses, trips and stumbles, through which I, ‘get up’ from, interrogate and learn through. In this exegesis I explain and question my trajectory of discovery, critically reflecting upon what has evolved and changed over these past two years, and what I have learned. I outline the key stages/works made through the iterations of my creative practice. I review the work of those I have read and looked at within this course of study (including but not limited to the work of Bas Jan Ader, Guy Debord and the Situationist International, Robert Filliou, Hamish Fulton, Janet Cardiff, James Tapsell-Kururangi, Rebecca Mayo, Kate Newby, Xin Cheng) analysing aspects of their work, ideas, and concepts that have resonated with me while considering their influence and impact within my making and learnings. The conceptual framework for this thesis includes engagement with discourses around performativity, settler-colonial legacies of colonisation, failure as a generative process, gender politics in relation to body stereotypes, and ways to re-think processes of learning. The praxis undertaken through this MFA has enabled me to arrive at a presentation of companion forms (including text, photographic images, traces of process, handmade and found objects/entities) that collectively offer a non-linear articulation of subjective understandings of place.
Figures 7, 10, 11, 13, 14 & 15 are re-used with permission.
Keywords: 360699 Visual arts not elsewhere classified